Randomized, crossover, controlled trial on the modulation of cardiac coronary sinus hemodynamics to develop a new treatment for microvascular disease: Protocol of the MACCUS trial - Ullrich, Helen; Olschewski, Maximilian; Münzel, Thomas; Gori, Tommaso (Frontiers in Cardiovascular Medicine, 2023)
Background: Microvascular angina (MVA) is a frequent condition for which our understanding of the disease pathophysiology and therapeutic perspectives remain unsatisfactory. The current study is designed to test whether an improvement in microvascular resistances could be achieved by elevating backward pressure in the coronary venous system, based on the hypothesis that an increase in hydrostatic pressure could cause a dilatation of the myocardial arterioles, resulting in a reduction of vascular resistances. This approach might have potential clinical implications, as it might suggest that interventions aimed at increasing coronary sinus (CS) pressure might result in a decrease in angina in this subset of patients. The aim of our single-center, sham-controlled, crossover randomized trial is to investigate the effect of an acute increase in CS pressure on a number of parameters of coronary physiology, including parameters of coronary microvascular resistance and conductance. Methods and analysis: A total of 20 consecutive patients with angina pectoris and coronary microvascular dysfunction (CMD) will be enrolled in the study. Hemodynamic parameters including aortic and distal coronary pressure, CS and right atrial pressure, and the coronary microvascular resistance index will be measured at rest and during hyperemia in a randomized crossover design during incomplete balloon occlusion ("balloon") and with the deflated balloon in the right atrium ("sham"). The primary end point of the study is the change in index of microvascular resistances (IMR) after acute modulation of CS pressure, while key secondary end points include changes in the other parameters. Discussion: The aim of the study is to investigate whether occlusion of the CS is associated with a decrease in IMR. The results will provide mechanistic evidence for the development of a treatment for patients with MVA.